Pre-Exposure Prophylaxis Training among Medical Schools in the United States - Robert L. Cooper; Mohammad Tabatabai; Paul D. Juarez; Aramandla Ramesh; Matthew C. Morris; Katherine Y. Brown; Thomas A. Arcury; Marybeth Shinn; Leandro A. Mena; Patricia-Matthews Juarez (SAGE Publishing, 2021)
Pre-Exposure Prophylaxis (PrEP) has been shown to be an effective method of HIV prevention for men who have sex with-men (MSM) and -transgender women (MSTGWs), serodiscordant couples, and injection drug users; however fewer than 50 000 individuals currently take this regimen. Knowledge of PrEP is low among healthcare providers and much of this lack of knowledge stems from the lack or exposure to PrEP in medical school. We conducted a cross sectional survey of medical schools in the United States to assess the degree to which PrEP for HIV prevention is taught. The survey consisted Likert scale questions assessing how well the students were prepared to perform each skill associated with PrEP delivery, as well as how PrEP education was delivered to students. We contacted 141 medical schools and 71 responded to the survey (50.4%). PrEP education was only reported to be offered at 38% of schools, and only 15.4% reported specific training for Lesbian, Gay, Bisexual, and Transgender (LGBT) patients. The most common delivery methods of PrEP content were didactic sessions with 11 schools reporting this method followed by problem-based learning, direct patient contact, workshops, and small group discussions. Students were more prepared to provide PrEP to MSM compared to other high-risk patients. Few medical schools are preparing their students to prescribe PrEP upon graduation. Further, there is a need to increase the number of direct patient contacts or simulations for students to be better prepared.